Activation of Platinum(IV) Prodrugs by Cytochrome c and Characterization of the Protein Binding Sites - Lasorsa, Alessia; Stuchlíková, Olga; Brabec, Viktor; Natile, Giovanni; Arnesano, Fabio (Molecular pharmaceutics, 2016)
Platinum(IV) complexes generally require reduction to reactive Pt(II) species to exert their chemotherapeutic activity. The process of reductive activation of (15)N-labeled (OC-6-43)-bis(acetato)diamminedichloridoplatinum(IV), in the presence of nicotinamide adenine dinucleotide (NADH) and horse heart cytochrome c (cyt c), was monitored by (1)H,(15)N-HSQC NMR spectroscopy and protein digestion experiments. It has been shown that cyt c plays a catalytic role in the transfer of two reducing equivalents from NADH to Pt(IV) species. Noncovalent interactions between reduced monoaqua cisplatin (cis-[PtCl((15)NH3)2(H2O)](+)) and the protein, in the proximity of the heme cofactor, and also covalent binding of platinum to the protein region around Met65 and Met80 take place.
Keywords: Mass Spectrometry; vysokoúčinná kapalinová chromatografie; Molecular Structure; cytochromy c; vazba proteinů; cytochrome c; vazebná místa; Antineoplastic Agents; Cytochromes c; platina; Platinum; cisplatina; Protein Binding; anticancer prodrugs; NAD; Cisplatin; magnetická rezonanční spektroskopie; molekulární struktura; reductive activation; Binding Sites; prekurzory léčiv; Chromatography, High Pressure Liquid; Prodrugs; protinádorové látky; hmotnostní spektrometrie; Pt(IV) complexes; Magnetic Resonance Spectroscopy